$\frac{2x-1}{5}$ -$\frac{x-2}{3}$ =$\frac{x+5}{6}$ +1 06/10/2021 Bởi Adalyn $\frac{2x-1}{5}$ -$\frac{x-2}{3}$ =$\frac{x+5}{6}$ +1
Đáp án + Giải thích các bước giải: `(2x-1)/(5)-(x-2)/(3)=(x+5)/(6)+1` `<=>(6(2x-1))/(30)-(10(x-2))/(30)=(5(x+5))/(30)+(30)/(30)` `<=>6(2x-1)-10(x-2)=5(x+5)+30` `<=>12x-6-10x+20=5x+25+30` `<=>12x-10x-5x=6-20+25+30` `<=>-3x=41` `<=>x=-(41)/(3)` Vậy `S={-(41)/(3)}` Bình luận
Đáp án + Giải thích các bước giải:
`(2x-1)/(5)-(x-2)/(3)=(x+5)/(6)+1`
`<=>(6(2x-1))/(30)-(10(x-2))/(30)=(5(x+5))/(30)+(30)/(30)`
`<=>6(2x-1)-10(x-2)=5(x+5)+30`
`<=>12x-6-10x+20=5x+25+30`
`<=>12x-10x-5x=6-20+25+30`
`<=>-3x=41`
`<=>x=-(41)/(3)`
Vậy `S={-(41)/(3)}`